Influence of the casting processes and aging times on the microstructure and hardness of AlSi\(_{12}\)Cu cast alloys - BEROUAL, Said; PAILLARD, Pascal; BORJON-PIRON, Yann (Journal of Metals, Materials and Minerals, 2025)
The present study investigated the effects of the casting processes and aging times on the micro-structure and hardness of commercial AlSi12Cu alloys. The primary goal was to assess how various aging times affect the maximum hardness of the alloy and to evaluate the influence of cooling rates on hardness values obtained from sand casting (SC) and High-pressure die casting (HPDC). For both casting alloys, the solution heat treatment was performed at 540℃, followed by quenching. The alloys were then aged at 180℃ for various durations, ranging from 10 min to 50 h. The results reveal significant microstructural changes in the size and morphology of the eutectic silicon and intermetallic phases between the SC and HPDC. The α-Fe intermetallics predominantly exhibit a Chinese-script morphology in SC, whereas in HPDC, they are primarily present as polyhedral particles. The maximum hardness peak was observed at 8 h of aging in SC; in HPDC, it was achieved at only 4 h of aging. The results of the hardness and X-ray diffraction (XRD) analyses exhibit consistent trends, strong alignment, and good agreement with each other. The HPDC process, combined with heat treatment, significantly enhances the mechanical properties of cast aluminum alloys.